Mir-190b negatively contributes to the Trypanosoma cruzi-infected cell survival by repressing PTEN protein expression - Monteiro, Cintia Junia; Antunes Mota, Suianne Leticia; Diniz, Livia de Figueiredo; Bahia, Maria Terezinha; Moraes, Karen C. M. [UNESP] (Fundaco Oswaldo Cruz, 2015)
Chagas disease, which is caused by the intracellular protozoan Trypanosoma cruzi, is a serious health problem in Latin America. The heart is one of the major organs affected by this parasitic infection. The pathogenesis of tissue remodelling, particularly regarding cardiomyocyte behaviour after parasite infection, and the molecular mechanisms that occur immediately following parasite entry into host cells are not yet completely understood. Previous studies have reported that the establishment of parasitism is connected to the activation of the phosphatidylinositol-3 kinase (PI3K), which controls important steps in cellular metabolism by regulating the production of the second messenger phosphatidylinositol-3,4,5-trisphosphate. Particularly, the tumour suppressor PTEN is a negative regulator of PI3K signalling. However, mechanistic details of the modulatory activity of PTEN on Chagas disease have not been elucidated. To address this question, H9c2 cells were infected with T. cruzi Berenice 62 strain and the expression of a specific set of microRNAs (miRNAs) were investigated. Our cellular model demonstrated that miRNA-190b is correlated to the decrease of cellular viability rates by negatively modulating PTEN protein expression in T. cruzi-infected cells.
Keywords: cardiac cellular model; microRNA; PTEN; Trypanosoma cruzi